2006
DOI: 10.1111/j.1600-0668.2006.00454.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of movements on contaminant transport in an operating room

Abstract: In real-life ventilated enclosures like operating rooms movements take place. Persons' movements may influence the local flow field as well as the contaminant field substantially. Most often movements are ignored in simulations due to the complexity of the phenomenon. This paper presents an indirect and simple method to consider the influence of movements that may enable modelers to include this important phenomenon in the engineering application of CFD. This may improve practical risk assessment--for instance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(62 citation statements)
references
References 19 publications
0
60
0
2
Order By: Relevance
“…First of all, no movement was simulated in the OR. Brohus [16] found that this has some influence on the particle distribution. This could contribute as well, especially in cases where the downflow area is relatively unstable.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…First of all, no movement was simulated in the OR. Brohus [16] found that this has some influence on the particle distribution. This could contribute as well, especially in cases where the downflow area is relatively unstable.…”
Section: Discussionmentioning
confidence: 98%
“…If measuring is impossible or impractical, it is also possible to do a simulation instead. [15][16][17][18] The VDI 2167 describes a way to test whether particles from the environment are able to penetrate the clean area and settle in the operating area. To perform an assessment according to VDI 2167, heated puppets have to be placed in the room.…”
Section: Introductionmentioning
confidence: 99%
“…Both experimental [12][13][14][15][16] and numerical methods [5,9,10,[17][18][19][20][21][22] have been adopted to study the induced air ow pattern due to obstacle motion. Since experimental measurement is timeconsuming and very expensive, Computational Fluid Dynamics (CFD) techniques have become powerful and e cient tools for studying engineering problems, including air ow and contaminant distribution in enclosures [10].…”
Section: Introductionmentioning
confidence: 99%
“…Actual comparison towards a specific performance indicator as assumed here was not performed, but the principle indicates that high level modeling may not provide other (integrated) answers. This certainly holds when other important parameters and boundary conditions are neglected or not well taken into account [27]. Generally an optimum will have to be searched for.…”
Section: Discussion Assessment Methodologymentioning
confidence: 99%